PCR-Based Detection of Cryptosporidium spp. and Enterocytozoon bieneusi in Farm-Raised and Free-Ranging Geese (Anser anser f. domestica) From Hainan Province of China: Natural Infection Rate and the Species or Genotype Distribution - Zhao, Wei; Zhou, Huan-huan; Ma, Tian-ming; Cao, Jianping; Lu, Gang; Shen, Yu-juan (Frontiers in Cellular and Infection Microbiology, 2019)
Cryptosporidium spp. and Enterocytozoon bieneusi are two important zoonotic pathogens that can infect humans and a broad range of animal hosts. However, few studies have been conducted to study infection of the two pathogens in domestic geese until now. The aims of the present study were to determine the prevalence of natural infection, and the species or genotype distribution of Cryptosporidium and E. bieneusi in farm-raised and free-ranging geese from Hainan Province of China. In total, 266 fecal samples of geese were collected (142 farm-raised and 124 free-ranging geese). Cryptosporidium spp. and E. bieneusi were identified by nested PCR and sequencing analysis of the SSU rRNA and the ITS region of the rRNA genes. A total of 4.1% (12/226) of the geese were positive for Cryptosporidium spp., with 0.7% identified in the farm-raised geese and 7.0% in the free-ranging geese. Two bird-adapted species/genotypes were identified: C. baileyi (n = 1) and Cryptosporidium goose genotype I (n = 11). Meanwhile, E. bieneusi was found in 13.9% (37/266) of geese, with 8.9% identified in the farm-raised and 21.8% in the free-ranging geese. Eleven genotypes of E. bieneusi were identified constituted with six known genotypes: D (n = 13), I (n = 5), CHG2 (n = 1), CHG3 (n = 5), and CHG5 (n = 1), and five novel genotypes named HNE-I to V (one each). All of the genotypes identified in the geese here belonged to zoonotic Groups 1 or 2. This study is the first to demonstrate the presence of Cryptosporidium spp. and E. bieneusi in domestic geese from Hainan, China, and provides baseline data that will be useful for controlling and preventing these pathogens in goose farms. The geese infected with E. bieneusi, but not with Cryptosporidium, should be considered potential public health threats.